Clathrin-Mediated Endocytosis Delivers Proteolytically Active Phytaspases Into Plant Cells - Trusova, Svetlana V.; Teplova, Anastasia D.; Golyshev, Sergei A.; Galiullina, Raisa A.; Morozova, Ekaterina A.; Chichkova, Nina V.; Vartapetian, Andrey B. (Frontiers in Plant Science, 2019)
Phytaspases belong to the family of plant subtilisin-like proteases and are distinct from other family members, as they have strict and rarely occurring aspartate cleavage specificity and unusual localization dynamics. After being secreted into the apoplast of healthy plant tissues, phytaspases are able to return back into cells that have been committed to cell death due to a variety of biotic and abiotic stresses. It was recently discovered that retrograde transport of phytaspases involves clathrin-mediated endocytosis. Here, consequences of phytaspase internalization were studied. Proteolytic activity of phytaspases in the apoplast and intracellular protein fractions obtained from Nicotiana benthamiana leaves containing either endogenous phytaspase only or transiently producing Nicotiana tabacum phytaspase-EGFP protein (NtPhyt-EGFP) was determined. We demonstrated that triggering phytaspase internalization by antimycin A-induced oxidative stress is accompanied by re-distribution of phytaspase activity from the apoplast to the cell interior. Inhibition of clathrin-mediated endocytosis by co-production of the Hub protein prevented phytaspase internalization and phytaspase activity re-localization. Specificity of endocytic uptake of phytaspases was demonstrated by the co-production of an apoplast-targeted mRFP protein marker, which retained its apoplastic localization when phytaspase internalization was essentially complete. Overproduction of NtPhyt-EGFP, but not of the proteolytically inactive phytaspase mutant, per se caused moderate damage in young Nicotiana benthamiana seedlings, whereas antimycin A treatment induced a pronounced loss of cell viability independent of the NtPhyt-EGFP overproduction. Interestingly, inhibition of clathrin-mediated endocytosis abrogated cell death symptoms in both cases. In contrast to stress-induced internalization of tobacco phytaspase, Arabidopsis thaliana phytaspase-EGFP protein (AtPhyt-EGFP) was spontaneously internalized when transiently produced in N. benthamiana leaves. The AtPhyt-EGFP uptake was dependent on clathrin-mediated endocytosis as well, the internalized protein being initially visualized within the membranous vesicles. At later time points, the EGFP tag was cleaved off from AtPhyt, though the elevated level of intracellular AtPhyt proteolytic activity persisted. Our data, therefore, point to clathrin-mediated endocytosis as a means to deliver proteolytically active phytaspases into plant cells. It would be interesting to learn whether or not phytaspases are unique among the large family of plant subtilisin-like proteases in their ability to utilize retrograde trafficking.